Upper and Lower Bounds for Ranks of the Matrix Expression X-XAX - Zhiping Xiong (Abstract and Applied Analysis)
We consider the question of how to take X such that the nonlinear matrix expression X-XAX attains its maximal and minimal possible ranks.